2020
DOI: 10.7717/peerj.8541
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere bacterial and fungal communities during the growth of Angelica sinensis seedlings cultivated in an Alpine uncultivated meadow soil

Abstract: Background: Angelica sinensis seedlings are grown in alpine uncultivated meadow soil with rainfed agroecosystems to ensure the quality of A. sinensis after seedling transplantation. The aim was to investigate the rhizosphere bacterial and fungal communities during the growth stages of A. sinensis seedlings. Methods: The bacterial and fungal communities were investigated by HiSeq sequencing of 16S and 18S rDNA, respectively. Results: Proteobacteria and Bacteroidetes were bacterial dominant phyla throughout grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…The site of cultivation is mountainous with meadow soil and a rainfed agroecosystem. It has a cool and semi-humid climate with an annual average temperature of 5–6 °C, approximately 2219 h annual sunshine, 90–120 frost-free days per year, and 451.4–817.8 mm of annual rainfall, mainly from June to September 60 .…”
Section: Methodsmentioning
confidence: 99%
“…The site of cultivation is mountainous with meadow soil and a rainfed agroecosystem. It has a cool and semi-humid climate with an annual average temperature of 5–6 °C, approximately 2219 h annual sunshine, 90–120 frost-free days per year, and 451.4–817.8 mm of annual rainfall, mainly from June to September 60 .…”
Section: Methodsmentioning
confidence: 99%
“…Proteobacteria and bacteroidetes were the dominant bacterial phyla throughout the growing season of A. sinensis , whereas fungal dominant phyla varied with growth periods. Furthermore, the plant weight, root length, root diameter, soil pH, rainfall, and climate temperature were the main factors contributing to the variation in microbial community composition of A. sinensis [ 15 ]. The most recent study on plant–microbe interactions mainly focused on succession cropping obstacles of medicinal plants, responses of plant–microbe to environmental stress, changes in rhizosphere nutrition conditions, root system biomass, and growth but provided little information on the accumulation of active constituents under different soil microenvironments [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that soil microorganisms play a key role in the transformation of material and energy in the micro-ecological environment of plant roots (Banerjee et al, 2016). The rhizosphere cultivable microbial community, fungal and bacterial diversity, and core bacterial community were signi cantly affected by continuous cultivation of A. sinensis seedlings (An et al, 2020). Imbalanced ammonia-oxidizing bacterial populations may lead to reduced growth of A. sinensis (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%